Impact of complex interventions on antibacterial therapy and etiological diagnostics in community-acquired pneumonia: a 12-month pre- and post-intervention study - Ablakimova, Nurgul; Rachina, Svetlana; Smagulova, Gaziza; Vlasenko, Anna; Mussina, Aigul; Zhylkybekova, Aliya; Yessenzhulova, Ardak; Koshmaganbetova, Gulbakit K.; Iztleuov, Yerbolat (Frontiers in Pharmacology, 2025)
BackgroundAntimicrobial resistance (AMR) is a growing global health concern, with community-acquired pneumonia (CAP) remaining a leading cause of hospitalization and empirical antibiotic use. However, adherence to clinical guidelines in CAP management is inconsistent, particularly in resource-limited settings.ObjectivesThis study aimed to evaluate the impact of a complex antimicrobial stewardship intervention on the quality of antibacterial therapy and diagnostic practices in hospitalized patients with CAP in Aktobe, Kazakhstan.MethodsA 12-month pre- and post-intervention study was conducted in two multidisciplinary hospitals. The intervention included educational sessions, implementation of protocol-based care, and improved access to diagnostic tools. Key indicators assessed included adherence to national antibiotic guidelines, use of severity scoring tools, timely antibiotic administration, microbiological diagnostics, and step-down therapy.ResultsSignificant improvements were observed in several indicators: guideline-adherent antibiotic prescribing increased from 75% to 93.5% (p < 0.001), step-down therapy from 2.7% to 8.2% (p = 0.021), and use of CURB-65/CRB-65 from 0% to 8.7% (p < 0.001). Use of urinary antigen tests increased from 0% to 12% (p < 0.001), while evaluation of antibiotic effectiveness at 48–72 h rose from 40.2% to 70.1% (p < 0.001). Multivariable logistic regression confirmed the independent impact of the intervention, adjusting for factors such as age, pneumonia severity, and shift type (day shift vs off-duty shift).ConclusionA targeted, context-specific intervention significantly improved key quality indicators in CAP management. These findings support the effectiveness of multifaceted stewardship strategies in improving clinical practice and mitigating AMR.